MODELING OF OIL SPILL ON MONTARA WELL HEAD PLATFORM IN THE TIMOR SEA - - Lukijanto; Andri Purwandani (Widyariset, 2012)
Modeling of oil spill on Montara well head platform in the Timor Sea, with short-term period from August 20,2009 until January 5, 2010 has been conducted. The purpose of this study was to examine the pattern of the spreadof oil spills (the distribution, the areas of oil exposure, concentration of the oil spill and the time of exposure)which was a possible entry into the Exclusive Economic Zone (EEZ) of Indonesia. The results indicated that an oilspill scenario of 400, 1,500 and 2,000 barrels per day were obtained the maximum value of the oil concentrationof 54.0 ppm, 202.4 ppm and 270 ppm, respectively. The total area of oil spill exposure in EEZ of Indonesia wasabout 41,360 km2 with an average maximum area exposed for 2 hours and a maximum of 3:29 hours. Comparisonbetween the results of oil spill modeling with image analysis of Modis Aqua and Terra (SkyTruth) were obtainedthat the extent of distribution and movement patterns differ from one to another. Furthermore, the verification andvalidation of the modeling results with the field data are still required.